Migration in towns in China, a tale of three provinces : evidence from preliminary tabulations of 2000 census - Shi, Anqing (Policy research working paper, 2006)
"There is a concern that the growth of towns in China has been stalled recently and with it, the creation of nonfarm jobs in rural industries. The author uses the 2000 census tabulations to look at this issue by examining in-migration in towns in three provinces in China-Zhejiang, Henan, and Sichuan-their educational attainment, original place, and occupational composition. In addition to the diversified patterns of town in-migrants revealed in the three provinces, the author finds that town in-migrants generally possess a higher level of educational attainment than the local population in towns, especially in the less developed western and central regions. This inflow of human capital could foster development in towns. There is also evidence that as economic opportunity increases in towns, such as in richer coastal province of Zhejiang, better educated people in rural areas are likely to shift their jobs from the farm to the nonfarm sector in towns nearby, instead of leaving the countryside to migrate to other provinces. This could reduce migration pressure on big cities. Finally, the labor market in towns in the less developed west and central regions is more flexible in accommodating in-migrants, whereas in the developed province of Zhejiang the labor market is segregated between migrants and the local population. "--World Bank web site